Epidemiology and Etiology of Acute Pancreatitis in Urban and Suburban Areas in Shanghai: A Retrospective Study - Junjie Fan; Ling Ding; Yingying Lu; Junyuan Zheng; Yue Zeng; Chunlan Huang (Gastroenterology Research and Practice)
Aim. To investigate the epidemiology, etiology, and severity of acute pancreatitis (AP) in urban and suburban areas of Shanghai in 2011 and 2016. Methods. A retrospective study of patients admitted to Shanghai General Hospital (urban and suburban campuses) with AP in 2011 and 2016 was undertaken. Patients were divided into acute biliary pancreatitis (ABP), hypertriglyceridemic pancreatitis (HTGP), alcoholic pancreatitis, and pancreatitis of other causes according to etiology. Severity of AP was divided into mild AP (MAP), moderately severe AP (MSAP), and severe AP (SAP). Results. AP patients in the suburban area increased more rapidly than those in the urban area. The mean onset age of AP in the urban area in 2016 was older than that in the suburban area (p<0.05). The suburban patients in 2016 have significantly younger mean onset age than those in 2011 (p<0.05). HTGP incidence in suburban patients increased from 2011 to 2016, which changed little in the urban area. Urban females were more likely to develop HTGP than suburban ones in 2011, which reversed in 2016. As to the male patients, the incidence of HTGP increased in both urban and suburban areas. Nonelderly (<60 years old) patients had higher HTGP incidence than elderly ones in both 2011 and 2016. The descending trend of SAP in the suburban area was more obvious than that in the urban area. The length of hospitalization decreased from 2011 to 2016, especially in SAP patients. Conclusions. AP patients increased more rapidly in the suburban area of Shanghai with younger onset age. The incidence of HTGP increased significantly in the suburban area, reminding of the prevention and screening of HTG.